EVALUASI ANTARMUKA GAME SAVE ME WHEN IS SLEEP MENGGUNAKAN METODE USABILITY TESTING - Tiowema Jastin Kusumajaya; Rifda Ainun Ufairah; Savilla Tifania Mahadewi; Ammar Naufal Khariullah; Rangga Putra Wardana; Benedictus Angelo Dwi Kusuma (Jurnal Teknik dan Science, 2022)
Save Me When I Sleep is a PC game in the hyper-casual genre that allows players to save characters from being chased by monsters by controlling them to a safe place. It tells the story of Jason as the main character who has nightmares every night being chased by a dog named Wombat. Because in his dream Jason couldn't fight Wombat, he kept running away from the dog. This game can be played by children to adults as entertainment in their spare time. Because Save Me When I Sleep is a casual game and can be played by various groups, this game must have good usability to make it easy to play. Therefore, we need to conduct tests with players to measure the quality of our game's usability. The method used in this test is the usability testing method. Testing is done by giving assignments to respondents to play games and use questionnaires. The results of this test are that the UI and UX menus of this game are good and effective, this is evidenced by the good results of the questionnaire.